Freestanding palladium nanonetworks electrocatalyst for oxygen reduction reaction in fuel cells. (4th January 2018) - Begum, Halima; Ahmed, Mohammad Shamsuddin; Cho, Sung; Jeon, Seungwon
Abstract: Still it's a main challenge to design of highly efficient electrocatalysts to reduce the high overpotential of the oxygen reduction reaction (ORR). The 1 dimensional (1D) palladium nanonetworks (Pd-Net) can be a promising alternative to platinum (Pt)-based electrocatalyst for ORR. In this study, the Pd-Net electrocatalysts have been synthesized via a simple wet-chemical method with the assistance of cetyltrimethylammonium bromide (CTAB) and zinc precursor. Further investigation indicates that the thickness of Pd-Net can be regulated by simply changing the molar ratio of CTAB and the 5 ± 0.1 nm is proven as an efficient ORR electrocatalyst without any support material. The freestanding 1D Pd-Net has shown 2.2 and 3.6-fold higher electrochemical surface area than that of commercially available Pt/C and homemade Pd nanoparticles (PdNPs) catalysts, respectively. As a result, it provides a higher density of ORR active sites and facilitated the electron transport. The Pd-Net catalyst shows 2.1 and 4.1 times higher mass activity and 1.3 and 3.1 higher specific activity at 0.85 V (vs. RHE) with better ORR kinetics than that of Pt/C and PdNPs, respectively. Additionally, the Pd-Net catalyst has been demonstrated a significant tolerance to the anodic fuels (i.e. methanol) and enhanced durability than the Pt/C and PdNPs catalysts for ORR. Graphical abstract: Highlights: Tunable Pd-Net has been developed for catalyzing ORR in alkaline electrolyte. The Pd-Net has shown 2.2- and 3.6-fold higher ECSA than Pt/C and PdNPs, respectively. The Pd-Net has shows 2.1 and 4.1 times higher MA than Pt/C and PdNPs, respectively. Pd-Net has proven better catalysis than Pt/C due to better crystalline porous network.